Poster 193: Increased Hip Distractability in the Revision Hip Arthroscopy Setting: A Comparison Between Revision and Native Contralateral Hips with an Intra-Operative Axial Stress Exam Under Anesthesia. Issue 7 (30th July 2022) - Tomasevich, Kelly; Ohlsen, Suzanna; O, Dillon; Featherall, Joseph; Aoki, Stephen; Mortensen, Alexander
Objectives: Hip instability secondary to capsular insufficiency is a cause of persistent pain and/or functional disability following primary hip arthroscopy in a poorly defined subset of patients. Further, an easily distractible hip exam under anesthesia is a finding that has been described in the diagnosis of hip instability; however, the exam has relied on subjective findings of a perceived looseness and has lacked objective criteria. The purpose of this study was to compare intraoperative hip joint distractibility between hips that previously underwent arthroscopic surgery and the contralateral hip with no history of surgical manipulation. Methods: Patients undergoing revision hip arthroscopy between April 2019 and December 2020, who previously underwent arthroscopic hip surgery for femoroacetabular impingement syndrome, were prospectively enrolled. Exclusion criteria was any contralateral hip surgery. Prior to instrumentation, fluoroscopic images of both hips were obtained at 25 lb traction intervals up to 100 lbs. Total joint space and distraction were measured at each traction interval. (Figure 1 ) Distraction was calculated as the difference between the baseline joint space and the total joint space at each subsequent traction interval. (Figure 2 ) Wilcoxon signed ranks tests and McNemar tests were used to compare distraction between revision and native contralateral hips. Results: Forty-seven patients were included. Mean distraction of operative hips was significantly greater than mean distraction of non-operative hips at traction intervals of 50 lbs (2.13 vs. 1.04 mm, p = 0.002), 75 lbs (6.39 vs. 3.70 mm, p < 0.001), and 100 lbs (8.24 vs. 5.39, p < 0.001) (Figure 3 ). Mean total joint space of operative hips was significantly greater than mean total joint space of non-operative hips at traction intervals of 50 lbs (6.60 vs. 5.39 mm, p < 0.001), 75 lbs (10.86 vs. 8.05 mm, p < 0.001), and 100 lbs (12.73 vs. 9.73, p < 0.001). A higher percentage of operative hips achieved all distraction thresholds, in 2-mm intervals up to 10-mm, at each traction interval (Table 1 ). Conclusions: In the majority of patients undergoing revision hip arthroscopy, previous arthroscopic hip surgery increases axial distractibility of the hip joint compared to the native contralateral hip at axial traction forces of 50-100 lbs. Increased axial distractibility following hip arthroscopy may be suggestive of hip instability, and can be assessed on a stress exam under anesthesia. Table 1. Total and percentage of hips achieving millimetric distraction thresholds in 2mm intervals up to 10mm in operative and native hips .